"Community and Public Cultural Space Transformations in Post-Soviet Armenia: A Case Study of Border Settlements" Project - Muradyan, Haykuhi; Yeranyan, Nzhdeh; Abrahamyan , Hamazasp; Safaryan, Anush (History and Culture, 2025)
The purpose of this article is to present the "Community and Public Cultural Space Transformations in Post-Soviet Armenia: A Case Study of Border Settlements" project, including its goals, objectives, and key achievements. Since the collapse of the Soviet Union, the study of transformations in public cultural spaces in Armenia's border settlements is considered an important topic in the humanities that requires multidisciplinary research. The project's goal is to explore the public and state perceptions of sacred and secular culture and their impact on changes in public cultural spaces.This research focuses on the ways in which society and state institutions have reinterpreted and repurposed Soviet cultural structures—such as culture houses, rural clubs, culture palaces, creative unions, regional and community museums, art schools, etc. Secondly, the study examines new cultural processes that have emerged in Armenia since independence, such as the widespread installation of illuminated and metallic crosses, modern memorial monuments (khachkars, fountains, etc.), and post-Soviet practices aiming to transform cultural landscapes into sacred spaces.
Keywords: border settlements; post-Soviet period; public cultural space; reuse (recycling) of Soviet cultural structures; secularization of public cultural space in the Soviet era and post-Soviet "sacralization"